Application of integrated methods to assess and characterise the hydrogeology of coastal aquifers in parts of Lagos, Southwest, Nigeria - Yusuf, Mumeen Adebayo (My University, 2020)
The scope of this Thesis was to apply integrated methods to characterise the groundwater systems of the Lagos Coastal Basin. Like every coastal area in the world, saline intrusion has been the major challenge threatening the fresh groundwater aquifers of the study area over the last couple of decades, and thus, necessitating its assessment. Environmental isotopes, being a reliable and standard tool in hydrological investigation, was employed in combination with geophysical and hydrogeochemical methods to study the coastal aquifer systems. Geophysical probing of the subsurface revealed an alternating sequence of clay and sand, constituting the major lithological units in the study area. The basin aquifers are hosted essentially by sands and clayey sand, while the modes of aquifer occurrences are unconfined to semi-confined and confined for shallow and deep aquifers, respectively. Hydrochemical interpretation identified a surficial thin layer of fresh groundwater overlying the main zone of saline intrusion, which essentially comprises Ca-HCO3 and Ca-Mg-HCO3, Ca-Mg-HCO3 and Ca-Mg-Cl-SO4 hydrochemical facies for both dry and wet seasons, whereas the surface waters are characterised by Mg-Cl and Na-Cl water types for the lagoon and the ocean, respectively. The evaluation of the chemical processes revealed the dominance of carbonate weathering in the shallow aquifer. Hydrochemical, statistical and geochemical model analyses identified that the groundwater chemistry is significantly controlled by water–rock interaction and ion exchange processes as well as anthropogenic activities. Stable isotopes revealed precipitation as the main source of recharge into the basin aquifer systems. Analyses of the 3 H and 14 C activities were in agreement, revealing an interesting fact about the increase in the groundwater residence time from the surface through deeper depths deducible from 3H values range between 0.1 TU and 2.8TU; 0.0 TU and 0.3 TU; and 14 C age range from 4350±10 to 1050±10 years and between 12030±69 and 7400±50 years for the shallow and deep aquifers, respectively. The mean residence time was supported by the aquifer systems‟ recharge which took place in Holocene for the shallow aquifer and Late Pleistocene–early Holocene for the deep aquifers evident from the calculated ambient temperature, 18 O and 14 C plots. The hydrogeological conceptual models showed that saline incursion severely impacted the second aquifer from a depth ≥20m to 170m in the western and central parts of the study. However, the observed local saline occurrence in places <20m was attributed to groundwater overexploitation. Conclusively, the hydrological systems of the Lagos coastal basin is continually being modified by both anthropogenic and natural activities that constitute not only a major threat to the groundwater sustainability of the Lagos coastal basin but can also consume the entire study area
A thesis submitted to the Faculty of Science, University of the Witwatersrand, in fulfilment of the requirements for the degree of Doctor of Philosophy in Geology (Hydrogeology), 2020